2013
DOI: 10.1614/wt-d-11-00144.1
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Glyphosate in Palmer Amaranth (Amaranthus palmeri) Populations from New Mexico Pecan Orchards

Abstract: Two populations of Palmer amaranth suspected of being resistant to glyphosate have been reported since 2007 in pecan orchards in Doña Ana County, New Mexico. The objectives of the study were to confirm and evaluate the level of resistance, to evaluate the effectiveness of alternative herbicide mechanisms of action, and to compare the cost of effective alternative herbicides for weed management in pecan orchards. Greenhouse experiments indicated that the resistant populations were able to survive glyphosate at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
6
13
1
1
Order By: Relevance
“…All other treatments resulted in 15% to 80% biomass reduction. Similarly, Mohseni-Moghadam et al (2013b) reported no difference in biomass reduction of two Palmer amaranth biotypes at 16 DAT with glufosinate (>97%) or dicamba (88%) applied POST. Likewise, Jhala et al (2014) reported < 80% biomass reduction of HPPD-and PSIIinhibitor-resistant Palmer amaranth with mesotrione, topramezone, atrazine, halosulfuron-methyl, fluthiacet-methyl, or bromoxynil applied POST at 21 DAT.…”
Section: Palmer Amaranth Biotypesmentioning
confidence: 95%
“…All other treatments resulted in 15% to 80% biomass reduction. Similarly, Mohseni-Moghadam et al (2013b) reported no difference in biomass reduction of two Palmer amaranth biotypes at 16 DAT with glufosinate (>97%) or dicamba (88%) applied POST. Likewise, Jhala et al (2014) reported < 80% biomass reduction of HPPD-and PSIIinhibitor-resistant Palmer amaranth with mesotrione, topramezone, atrazine, halosulfuron-methyl, fluthiacet-methyl, or bromoxynil applied POST at 21 DAT.…”
Section: Palmer Amaranth Biotypesmentioning
confidence: 95%
“…Subsequently, a North Carolina GR A. palmeri population was reported with EPSPS gene duplication from 22‐ to 63‐fold . A New Mexico GR A. palmeri population was sevenfold more resistant than a GS population and had EPSPS gene duplication ranging from two‐ to tenfold, and individuals with EPSPS gene duplication were able to survive label‐rate glyphosate applications (0.82 kg ha −1 ) …”
Section: Gene Duplicationmentioning
confidence: 99%
“…57 A New Mexico GR A. palmeri population was sevenfold more resistant than a GS population and had EPSPS gene duplication ranging from two-to tenfold, and individuals with EPSPS gene duplication were able to survive label-rate glyphosate applications (0.82 kg ha −1 ). 58,59 Additional species have recently been reported with EPSPS gene duplication in GR populations, including L. multiflorum, 60 Kochia scoparia, 61 A. tuberculatus 62 and A. spinosus 63 (summarized in Table 1). The reported number of duplicated EPSPS gene copies in K. scoparia and A. tuberculatus populations is lower (from fourto tenfold) than the Georgia, North Carolina and Mississippi 55 -57 A. palmeri populations (Table 1), and similar to the New Mexico A. palmeri population.…”
Section: Epsps Gene Duplicationmentioning
confidence: 99%
“…In these cases, the target-site mechanism of resistance detected in Eleusine indica and the selective sequestration of glyphosate into vacuoles (non-target site mechanism) observed in C. canadensis would be similarly inherited (Ng et al, 2004b;Ge et al, 2010). On the other hand, the variable number of EPSPS copies explains the different glyphosate sensitivities in resistant A. palmeri and could influence the type of glyphosate resistance inheritance, determining whether it is monogenic or polygenic (Chandi et al, 2012;Mohseni-Moghadam et al, 2013).…”
Section: Cross-breedingmentioning
confidence: 99%